PICTURE OF SEXUAL FUNCTION IN CHRONIC KIDNEY FAILURE PATIENTS IN THE HEMODIALIS UNIT OF PROF. DR. H. ALOEI SABOE HOSPITAL, GORONTALO CITY - Sri Rahayu A. Aswadi; Nurdiana Djamaluddin; Nirwanto K. Rahim (PT. Jurnal Center Indonesia Publisher, 2025)
Fail kidney chronic (GGK) is disease progressive that requires therapy replacement kidney like hemodialysis . One of the common complications​ No realized is dysfunction sexual , which can lower quality life patient . Research This aiming For describe function sexual intercourse in GGK patients undergoing hemodialysis at Aloei Saboe Regional Hospital, Gorontalo City. Research design use approach descriptive quantitative with accidental sampling technique on 70 respondents who met the requirements criteria inclusion . Instruments used​ is IIEF questionnaire for men and FSFI for women . The results show that in patients male , function best orgasm (65.1%), followed by function erection (58.1%), desire sexual , and satisfaction connection sexual (51.2%). However , the desire sexual in a way overall disturbed (62.8%). In patients women , lubrication and desire sexual prominent (63%), followed by orgasm and comfort moment relate sexual (55.6%), with satisfaction sexual as function lowest (48.1%). In conclusion , patients man more Lots experience disturbance of desire sexual , while patient Woman experience more disturbance​ evenly distributed . It is recommended that the power health give education , counseling , and support psychosocial For increase quality life patient .